Chromosomal translocations induced at specified loci in human stem cells - Brunet, Erika; Simsek, Deniz; Tomishima, Mark; DeKelver, Russell; Choi, Vivian M; Gregory, Philip; Urnov, Fyodor; Weinstock, David M; Jasin, Maria (Proceedings of the National Academy of Sciences - PNAS, 2009)
The precise genetic manipulation of stem and precursor cells offers extraordinary potential for the analysis, prevention, and treatment of human malignancies. Chromosomal translocations are hallmarks of several tumor types where they are thought to have arisen in stem or precursor cells. Although approaches exist to study factors involved in translocation formation in mouse cells, approaches in human cells have been lacking, especially in relevant cell types. The technology of zinc finger nucleases (ZFNs) allows DNA double-strand breaks (DSBs) to be introduced into specified chromosomal loci. We harnessed this technology to induce chromosomal translocations in human cells by generating concurrent DSBs at 2 endogenous loci, the PPP1R12C/p84 gene on chromosome 19 and the IL2Rgamma gene on the X chromosome. Translocation breakpoint junctions for t(19;X) were detected with nested quantitative PCR in a high throughput 96-well format using denaturation curves and DNA sequencing in a variety of human cell types, including embryonic stem (hES) cells and hES cell-derived mesenchymal precursor cells. Although readily detected, translocations were less frequent than repair of a single DSB by gene targeting or nonhomologous end-joining, neither of which leads to gross chromosomal rearrangements. While previous studies have relied on laborious genetic modification of cells and extensive growth in culture, the approach described in this report is readily applicable to primary human cells, including multipotent and pluripotent cells, to uncover both the underlying mechanisms and phenotypic consequences of targeted translocations and other genomic rearrangements.